Determinan Wirausaha Perempuan Pengguna Transaksi Digital Selama Pandemi Covid-19 Di Indonesia - Asrofi, Dien Amalina Nur; Pratomo, Devanto Shasta; Pangestuty, Farah Wulandari (Jurnal Ekonomi Indonesia, 2022)
This study aims to examine the factors that influence women entrepreneurs to use digital transactions for their business ventures during the COVID-19 pandemic in Indonesia. The data used in this study is individual data sourced from the 2020 National Labor Force Survey (Sakernas). Sakernas is a labor force survey conducted by the Central Statistics Agency (BPS) on individual socio-demographic information, education, and employment. Binary logistic regression model was used to answer the research objectives. The results showed that the variables of age, college education, high school / vocational education, living in urban areas, having experience, and training and business fields in the trade sector had a positive effect on the tendency of women entrepreneurs to use digital transactions. Meanwhile, age, marital status and number of household members have a negative effect on the opportunities for women entrepreneurs to use digital transactions. By using digital transactions, it is hoped that it will further facilitate and expand the access of women entrepreneurs in maintaining their businesses, especially during the Covid-19 pandemic in Indonesia.